Loss-of-function mutations with circadian rhythm regulator Per1/Per2 lead to premature ovarian insufficiency†. Issue 4 (18th November 2018) - Zheng, Yating; Liu, Chao; Li, Yan; Jiang, Haijuan; Yang, Peixin; Tang, Jing; Xu, Ying; Wang, Han; He, Yulong
Abstract: The mechanism underlying premature ovarian insufficiency remains incompletely understood. Here we report that mice with Per1 m/m ; Per2 m/m double mutations display a decrease in female fertility starting approximately at 20 weeks old, with significantly less pups born from 32 weeks old onwards. Histological analysis revealed that a significant reduction of ovarian follicles was observed in the Per1/Per2 mutants compared with the littermate controls examined at 26 and 52 weeks old, while the difference was not statistically significant between the two groups at 3 and 8 weeks old. We further showed that vascular development including the ovarian follicle associated vascular growth appeared normal in the Per1/Per2 mutant mice, although clock genes were reported to regulate angiogenesis in zebrafish. The findings imply that loss-of-function mutations with Per1/Per2 result in a premature depletion of ovarian follicle reserve leading to the decline of reproductive capacity. Abstract : Disruption of circadian rhythm or its underlying regulatory network contributes to the premature depletion of ovarian follicle reserve.